Clinical Features and Management of Community-Acquired Pneumonia (CAP) In The Elderly - Arimbi, Muzaijadah Retno; Amori, Lakcandra Amar; Soetedjo, Farida Anggraini; Haryanti, Elizabeth; Yaniari, Roethmia (Jurnal Health Sains, 2025)
Community-Acquired Pneumonia (CAP) or pneumonia acquired outside health facilities is one of the main causes of morbidity and mortality in the elderly age group. As we age, immune function decreases and is accompanied by comorbidities such as diabetes, heart disease, and chronic lung disease that worsen the course of the disease. This study aims to find out the clinical picture and management of Community-Acquired Pneumonia (CAP) in the elderly. This study uses qualitative research methods. The data collection technique in this study is by studying case report documents. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results show that Community-Acquired Pneumonia (CAP) in the elderly is a complex condition with challenges in diagnosis and management, as the symptoms are often atypical and involve various risk factors. Clinical guidelines emphasize the importance of basic supporting examinations such as thoracic imaging and organ function evaluations, as well as prompt and appropriate administration of empirical antibiotics. Treatment should be adjusted to the severity of the patient's frailty, comorbidities, and frailty status. Supportive therapy plays an important role in recovery, while an individualized approach based on risk factors such as malnutrition, sarcopenia, and aspiration is needed to improve prognosis and lower mortality in the elderly with CAP.